Measurement-based care in forensic psychiatry. (January 2021) - Glancy, Graham; Choptiany, Maxym; Jones, Roland; Chatterjee, Sumeeta
Abstract: Measurement-based care (MBC) is the systematic evaluation of a patient's symptoms or factors before or during an encounter. It is used to inform treatment and behavioral health interventions. This article argues that MBC is the natural consequence flowing from evidence-based practice. In this article, MBC is defined and explained in detail. Barriers to the implementation of MBC are presented and methods of selecting a measurement tool are evaluated. The article describes areas where MBC can be applied in forensic settings, and specific risk assessment tools are presented and evaluated, including the HCR-20 v3, DASA-IV, DUNDRUM, and CGIC. The article emphasizes how imperative it is that physicians use MBC and discusses why forensic practice is ideally suited to MBC.